EPA enriched ethanolamine plasmalogens significantly improve cognition of Alzheimer's disease mouse model by suppressing β-amyloid generation. (February 2018) - Che, Hongxia; Zhou, Miaomiao; Zhang, Tiantian; Zhang, Lingyu; Ding, Lin; Yanagita, Teruyoshi; Xu, Jie; Xue, Changhu; Wang, Yuming
Graphical abstract: Highlights: EPA-pPE exerted better effects than EPA-PE and Egg-PE in suppressing Aβ generation. EPA-pPE obviously improved cognition of high-fat feeding SAMP8 mice. EPA-pPE suppressed oxidative stress, hyper-phosphorylated tau, neuro-inflammation and apoptosis. EPA-pPE might be applied as functional ingredients to relieve neurodegenerative disease. Abstract: EPA enriched ethanolamine plasmalogens (EPA-pPE) are important bioactive components and widely distributed in multifarious marine products. In the present study, Chinese hamster ovary cells stably transfected with APP751 and PS1 (CHO-APP/PS1 cells) and high-fat feeding SAMP8 mice were used to study the effects of EPA-pPE on Alzheimer's disease (AD). The in vitro experiments showed that EPA-pPE exerted better effects than EPA-PE and Egg-PE in decreasing the intracellular and extracellular Aβ levels. EPA-pPE obviously improved learning and memory function of high-fat feeding SAMP8 mice by Morris maze test. Further mechanism research indicated that EPA-pPE could significantly improve cognition of Alzheimer's disease by suppressing β-amyloid generation via reducing levels of APP and altering APP cleavage, thereby inhibiting oxidative stress, hyper-phosphorylated tau, neuro-inflammation and apoptosis. These results suggested that EPA-pPE might be applied as food supplements and/or functional ingredients to relieve neurodegenerative disease.